Improved Antitumor Efficiency of N4-Tetradecyloxycarbonyl Gemcitabine-Loaded Liposomes for Pancreatic Cancer Chemotherapy - Wang D; Wang X; Li Y; Wang X; Wang X; Su J; Wang A; Lv K; Liu M; Xia G (International Journal of Nanomedicine)
Dan Wang,* Xiaobo Wang,* Yan Li, Xiaowei Wang, Xuelei Wang, Jiayi Su, Apeng Wang, Kai Lv, Mingliang Liu, Guimin Xia Institute of Medicinal Biotechnology, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100050, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guimin Xia; Apeng Wang, Email xiaguimin@126.com; wangapeng@imb.pumc.edu.cnBackground: Gemcitabine (Gem) is one of the first-line chemotherapy drugs for pancreatic cancer treatment. However, its short half-life in plasma and adverse effects limited its broader application.Methods: A novel Gem derivative (N4-tetradecyloxycarbonyl gemcitabine, tcGem) was synthesized and encapsulated into liposomes (LipotcGem) to overcome the above shortcomings.Results: LipotcGem has been successfully formulated, with the average size of 115 nm, zeta potential values of − 36 mV, encapsulation efficiency of up to 98%, and drug loading capacity of 8.1%. Compared to Gem, LipotcGem improved in vitro antitumor activity significantly, as evidenced by the lower IC50, the higher percentage of apoptotic cells, the stronger ability to inhibit cell migration and invasion due to the higher cellular accumulation (100 times). Additionally, the endocytosis of LipotcGem was mainly mediated by caveolae, and was then processed in the lysosome, where tcGem was released and hydrolyzed into Gem. LipotcGem inhibited tumor growth by 70% in subcutaneous xenograft model and 90% in orthotopic xenograft model, respectively. LipotcGem suppressed tumor metastasis and prolonged survival without perceptible systemic toxicity, which may be caused by the longer t1/2 in vivo (3.5 times, 5.23 vs 1.46 h) and more enrichment in tumor tissue (750 times).Conclusion: LipotcGem significantly increased the anti-tumor efficiency and decreased the toxicity for chemotherapy of pancreatic cancer. Keywords: pancreatic cancer, gemcitabine, N4-tetradecyloxycarbonyl gemcitabine, liposomes